ANALISIS EFISIENSI USAHATANI MAWAR DI PROVINSI JAWA TENGAH - Levana Masitajasmin Putri; Netti Tinaprilla; Yusalina Yusalina (Politeknik Negeri Lampung., 2023)
This study aims to analyze the factors that influenced the production of roses and the level of technical, allocative, and economic efficiencies of rose farming in Central Java along with the factors that influenced them. This study employed Stochastic Frontier Analysis (SFA) and dual cost reduction methods. The findings of this study indicate that only three variables had a significant effect on rose production in Central Java, namely land area, number of plants, and chemical fertilizers. Furthermore, in terms of the level of efficiency, rose farming in Central Java had been said to be technically efficient but had not been considered to be efficient in terms of its allocation and economic factors with an average score of technical, allocative, and economic efficiencies of 0.82, 0.33, and 0.28. Socio-economic factors that significantly affected technical inefficiency were the source of seeds, business assistance, and partnership. Meanwhile, the variables that had a significant effect on allocative inefficiency and economic inefficiency were the proportion of self-financing sources, farmers group membership, and partnerships. Keywords: dual cost, efficiency, stochastic frontier, rose farming